2020
DOI: 10.25046/aj050652
|View full text |Cite
|
Sign up to set email alerts
|

Effective Learning of Tax Regulations using Different Chatbot Techniques

Abstract: Teaching tax-related regulations have always been a challenge due to the inclusion of external variables that hinder the learning process, such as the high complexity of tax systems and legislation variability. Universities have sought different alternatives to support the teaching process both outside and inside the classroom, ranging from recreational activities to active learning. This article will show the experience resulting from using a chatbot to support learning in accounting students for the teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
2
0
2
Order By: Relevance
“…The teaching agent simply mimics a tutor by presenting scenarios to be discussed with students. In other studies, the teaching agent emulates a teacher conducting a formative assessment by evaluating students' knowledge with multiple-choice questions (Rodrigo et al, 2012;Griol et al, 2014;Mellado-Silva et al, 2020;. Moreover, it has been found that teaching agents use various techniques to engage students.…”
Section: Teaching Agentsmentioning
confidence: 99%
“…The teaching agent simply mimics a tutor by presenting scenarios to be discussed with students. In other studies, the teaching agent emulates a teacher conducting a formative assessment by evaluating students' knowledge with multiple-choice questions (Rodrigo et al, 2012;Griol et al, 2014;Mellado-Silva et al, 2020;. Moreover, it has been found that teaching agents use various techniques to engage students.…”
Section: Teaching Agentsmentioning
confidence: 99%
“…As principais atividades para o desenvolvimento das habilidades pode ser mediante a adoção do método socrático, isso é, questionamentos aos estudantes durante a aula (Blankley et al, 2017); o uso de aulas invertidas (Brown et al, 2016); aprendizado cooperativo e colaborativo (Blankley et al, 2017); aplicação de estudos de caso para desenvolvimento da análise e discussão . E, com o avanço tecnológico, os docentes também podem adotar fóruns on-line, blogs, salas de bate papo, sistema de respostas, como o clickers, Kahoot, entre outros (Grávalos-Gastaminza et al, 2022;Krom, 2012;Mellado-Silva et al, 2020).…”
Section: Referencial Teóricounclassified
“…O feedback dos alunos indicou que a tarefa melhorou seu aprendizado de conhecimento técnico tributário, exigiu que fossem criativos e originais, encorajou-os a fazer ligações entre conceitos tributários relacionados e os motivou a usar os recursos de pesquisa de forma mais eficaz. Mellado-Silva et al (2020), com a aplicação de um chatbot para o ensino de regulamentos tributários do Chile, também verificaram sua eficácia em acordo com o melhor desempenho dos alunos.…”
Section: Análise E Discussão Dos Estudosunclassified
“…One potential benefit is the ability for ChatGPT to assist with generating and answering multiple choice questions, providing students with instant feedback, and allowing them to quickly assess their understanding of the material. This can be seen in the study " Effective learning of tax regulations using different chatbot techniques" by Mellado-Silva et al [27], which found that the use of AI in education led to improved student performance on multiple choice assessments. Furthermore, ChatGPT can potentially facilitate more dynamic discussions.…”
Section: Discussionmentioning
confidence: 94%